Remove Noise from Grayscale Digital Images by Traditional and Fuzzy Filters - Baydaa Khalil (Al-Rafidain Journal of Computer Sciences and Mathematics)
Image denoising and enhancement is an important field and it is used very much in image processing, where images are corrupted by many kinds of noise, therefore, methods and techniques must be used to remove these noises. In this research seven traditional filters are used to remove noise from digital images corrupted with salt&pepper noise and Gaussian noise. And also adopting principle of fuzzy logic to hybrid between traditional filters and fuzzy logic using double bell shaped membership function and also hybrid with double adjusted sigmoid  membership function to create seven fuzzy sigmoidal filters. After applying seven traditional methods, seven fuzzy bell methods and seven fuzzy sigmoidal methods , by using measures of restored image PSNR, MSE, MAE , shows the final methods i.e. seven fuzzy sigmoidal methods are better than other filters i.e. methods that are used in this research after comparing the results.